DEFORESTATION AND COMPENSATION FOR THE SURROUNDING COMMUNITY FROM A LEGAL PERSPECTIVE - yanti fristikawati; nugroho adipradana; samuel hutabarat (Jurnal Paradigma Hukum Pembangunan, 2026)
Forests are the lungs of the world, benefiting both the environment and the communities surrounding them. Forest destruction, including through deforestation, will have detrimental impacts on society. Some of the detrimental impacts that can occur with deforestation are: landslides and floods have damaged both medicinal and community-owned crops. This means local communities cannot utilize the forest. The problem that will be discussed in this article is how to regulate forest protection, and if deforestation occurs, can the community receive compensation? The method used in this research is normative juridical, which studies more about the existing regulations in Indonesia regarding environmental protection, especially forests. From the research results it can be seen that the existing regulations are sufficient to protect forests, however, compensation for the community has not yet been regulated.             Things that can be done regarding the losses experienced by communities due to deforestation include restoring the environment and helping communities to meet their needs. Environmental restoration and assistance to the community can be carried out by companies that manage forests, or the government, especially if the forest is a customary forest or state forest.